2019
DOI: 10.1126/scirobotics.aau9757
|View full text |Cite
|
Sign up to set email alerts
|

On the choice of grasp type and location when handing over an object

Abstract: The human hand is capable of performing countless grasps and gestures that are the basis for social activities. However, which grasps contribute the most to the manipulation skills needed during collaborative tasks, and thus which grasps should be included in a robot companion, is still an open issue. Here, we investigated grasp choice and hand placement on objects during a handover when subsequent tasks are performed by the receiver and when in-hand and bimanual manipulation are not allowed. Our findings sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 57 publications
2
86
0
1
Order By: Relevance
“…(2) the orientation of the object toward the receiver; and (3) which part of the object is offered unobstructed (Cakmak et al, 2011a;Cini et al, 2019). Previous studies suggested that it is the passer who mainly selects the handover location (Shibata et al, 1995) and can use subtle cues, such as shared gaze, to dictate it (Moon et al, 2014).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) the orientation of the object toward the receiver; and (3) which part of the object is offered unobstructed (Cakmak et al, 2011a;Cini et al, 2019). Previous studies suggested that it is the passer who mainly selects the handover location (Shibata et al, 1995) and can use subtle cues, such as shared gaze, to dictate it (Moon et al, 2014).…”
Section: Related Workmentioning
confidence: 99%
“…Thereby, a protocol must include a subsequent task to aim at evaluating the quality of the humanrobot collaboration (Ortenzi et al, 2019). Our previous study on humans (Cini et al, 2019) suggested that during a handover, human passers adjust both their grasp type and location to better accommodate the receiver's needs. While power grasps, that are stable and enveloping, are favored for a direct use of the object, passers preferred precision grasps leaving most of the object available during a handover.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Each attribute is also assigned one or two digits of binary code. The codes are then combined in order to create a machine representation of the motion; for example, motion code {10111010} means that we have a contact motion (1) of a rigid engagement type (0) which causes a movement of the acted-upon passive object (11), it has a prismatic but non-revolute trajectory motion (1 and 0), a continuous contact type (1), and the motion is typically unimanual (0).…”
Section: A Motion Attributesmentioning
confidence: 99%
“…Those studies have focused on uncovering more than the dichotomy between power and precision grasps, and they go deep into the way fingers secure objects contained within the hand. Grasping taxonomies have greatly aided in grasp planning for robot manipulation [9], [10], [11]. To some degree, this relates to the theory of affordance [12] where we can infer the functionality of an object based on properties of the object itself.…”
Section: Introductionmentioning
confidence: 99%